USE OF HANDCUFFS IN THE JURY COURTROOM: EXCEPTIONALITY, WRITTEN JUSTIFICATION, AND EFFECTS ON THE VERDICT (CIPEEX, 2025)
This paper examines the use of handcuffs in Brazilian jury trials in light of the Federal Supreme Court’s Binding Precedent No. 11 and the Code of Criminal Procedure, determining when restraint is lawful, how it must be justified, and whether it may bias jurors. The aim is to delineate the exceptional nature of the measure, the requirement of written reasoning and record, and the procedural consequences of non-compliance (nullity and potential liability), while assessing impacts on human dignity and the presumption of innocence. Methodologically, it adopts a bibliographic, inductive approach based on documentary analysis of the CPP (Decree-Law No. 3,689/1941) and Binding Precedent No. 11, and discusses whether displaying a handcuffed defendant influences the verdict. The findings indicate that handcuffs are permissible only in cases of resistance, well-founded risk of escape, or danger to physical integrity, and the decision must be expressly recorded; exhibiting a handcuffed defendant may stigmatize him before the Jury Panel, so judges should prevent undue contamination and order removal when appropriate. It concludes that restraint is exceptional and dependent on written justification; disregard of the legal parameters entails nullity and potential liabilities, whereas judicial caution preserves dignity, the presumption of innocence, and the integrity of the verdict.
Keywords: binding precedent no. 11; handcuffs; jury court; Human dignity